There is no such thing as a social science in defence of Peter Winch - Hutchinson, Phil; Read, Rupert J. 1966-; Sharrock, Wes W. 1943- (Ashgate, 2008)
What does Peter Winch mean by his claim that there is no such thing as a social science? Debates in philosophy and sociology about foundational questions of social ontology and methodology often claim to have adequately incorporated and moved beyond Winch's concerns.
Introduction: The legendary PC -- Beyond pluralism, monism, relativism, realism, etc. : reassessing Peter Winch -- Winch and linguistic idealism -- Seeing things for themselves : Winch, ethnography, ethnomethodology, and social studies -- Winch and conservatism : the question of philosophical quietism. -- Includes index.
Keywords: Winch, Peter; Winch, Peter -- 1926-1997; Philosophy and social sciences; Sozialphilosophie